Waffle Slab Behavior Subjected to Blast Load - Ghasem Gorji Bandpey; Gholamreza Abdollahzadeh; Ali Rahmani (Civil Engineering Infrastructures Journal, 2021)
Over the previous years, the use of structure roof systems which can be implemented with long column spans has been welcomed by manufacturers. One of the most widely used roofs is the waffle slab system. Therefore, by reviewing previous studies in the field of roof collapse in reinforced concrete structures under blast, the absence of studies on the performance of waffle slab and comparing its behavior with blast affected RC slabs is observed. Laboratory simulation of this problem requires high cost, high accuracy in model building and much time. In this study, after preliminary model validation with experimental research and two numerical studies in LS-DYNA software, the behavior of waffle slab subjected to blast load and compare its performance with RC slab are investigated. It should be noted that because the blast load is applied to the structure in a very short time, it has a high loading rate. Therefore, the strain rate effects on concrete and reinforcement are considered for achieving real material behavior. The identical volume of concrete and reinforcement used in all roofs is considered in order to evaluate and compare the behavior of the roofs reasonably. Then, the effect of the geometric dimension of waffle molds and the effect of the supporting condition on the Waffle slab responses are studied. Other investigated parameter in this study includes the effect of concrete compressive strength on the behavior of roof under blast load. The mass of the explosive and its distance from the roof surface are other parameters considered in this study. The effect of bar size on the behavior of the roof is also investigated. The results of this study are presented as diagrams and tables showing that given the same volume of concrete and reinforcement in the RC slab and the waffle slab, the central displacement of Waffle slab is reduced to a desirable level. This shows the better behavior of the waffle slab in comparison with the RC slab with the same volume of material under the blast load.